Measurement report: Oxidation potential of water-soluble aerosol components in the south and north of Beijing - W. Yuan; R.-J. Huang; C. Luo; L. Yang; W. Cao; J. Guo; H. Yang (Atmospheric Chemistry and Physics)
Water-soluble components significantly contribute to the oxidative potential (OP) of atmospheric fine particles (PM2.5), but our understanding of the water-soluble PM2.5 OP and its sources, as well as its relationship with water-soluble components, is still limited. In this study, the water-soluble OP levels in wintertime PM2.5 in the south and north of Beijing, representing the difference in sources, were measured with the dithiothreitol (DTT) assay. The volume-normalized DTT (DTTv) in the north (3.5±1.2 nmol min−1 m−3) was comparable to that in the south (3.9±0.9 nmol min−1 m−3), while the mass-normalized DTT (DTTm) in the north (65±28 pmol min−1 µg−3) was almost twice that in the south (36±14 pmol min−1 µg−3). In both the south and north of Beijing, DTTv was better correlated with soluble elements instead of total elements. In the north, soluble elements (mainly Mn, Co, Ni, Zn, As, Cd and Pb) and water-soluble organic compounds, especially light-absorbing compounds (also known as brown carbon), had positive correlations with DTTv. However, in the south, DTTv was mainly related to soluble As, Fe and Pb. The sources of DTTv were further resolved using the positive matrix factorization (PMF) model. Traffic-related emissions (39 %) and biomass burning (25 %) were the main sources of DTTv in the south, and traffic-related emissions (>50 %) contributed the most to DTTv in the north. Our results indicate that vehicle emission was an important contributor to the OP in Beijing ambient PM2.5 and suggest that more study is needed to understand the intrinsic relationship between the OP and light-absorbing organic compounds.